Korelasi Antara Prophetic Intelligence (Kecerdasan Kenabian) Terhadap Prestasi Belajar PAI Di SMP Al-Furqan MQ Tebuireng Jombang - Askoning; Haris Supratno; Hanifuddin; Khoirotul Idawati (Sekolah Tinggi Ilmu Tarbiyah Al-Bukhary Labuhanbatu, 2025)
This study is a study used to find and describe whether there is a relationship or correlation between prophetic intelligence and learning achievement at SMP aL-Furqan MQ. Prophetic intelligence is a method of intelligence that does not only see a person's ability from their intellectual intelligence, but also from their spiritual and bathiniyyah or heart aspects This study uses a quantitative approach with the correlation method. Correlation is a statistical analysis technique to find the relationship between two variables. The relationship between the two variables can occur because of a causal relationship or just a coincidence. The design of this study was to distribute a questionnaire containing questions about Prophetic Intelligence (x) and PAI report card scores as a learning achievement variable (Y). Based on the results obtained, the Prophetic Intelligence of AL-Furqan MQ Tebuireng Jombang Middle School students is included in the Medium category with 57 students with a percentage of 55%. The learning achievement of AL-Furqan MQ Tebuireng Jombang Middle School students is included in the Medium category with 53 students with a percentage of 51%. And there is a correlation between Prophetic Intelligence and PAI learning achievement, by 39% or 0.390> 0.05. that means, that every increase in the value of Prophetic Intelligence will also increase the value of PAI learning achievement.